Evaluation and ranking of selected hospitals in Mashhad in terms of quality of services provided by the method of FAHP and GRA-TOPSIS - Somayeh Fadaei; Mostafa Kazemi; Fateme Nezhad Shokoohi (Tehran University of Medical Sciences, 2020)
Background: Assessing and improving the quality of services in hospitals because deal with the health of humans is very important. The purpose of this study is to identify and weigh quality criteria and ranking of four hospitals in Mashhad.   Materials & Methods: The present study is of type  Applied Studies  that is a cross-sectional study conducted in the winter of 1396. In this study, by literature review, dimensions of service quality in the hospital was identified. Then, a paired comparison questionnaire (including 8 people) was used to conduct the survey. Then coefficients of importance of each dimension were calculated through the process of hierarchical analysis in a fuzzy environment. Decision-making matrix questionnaire was completed by a 400-person sample of patient companions in four hospitals.Then, hospitals were ranked using GRA-TOPSIS method. The validity of questionnaires were confirmed by the expert group.   Results:Using FAHP, knowledge and skills of medicine obtained the most important coefficient. Also, using GRA-TOPSIS, third hospital received the fourth place in the provision of services. Also in the third hospital the quality of access requires the greatest improvement.   Conclusion: In addition to ranking hospitals based on quality of service criteria, the GRA-TOPSIS method is able to identify each hospitalchr('39')s weaknesses in each criterion. As a result, the priorities for improving the quality of service in each hospital were identified, and the hospital manager could work to improve performance on the criteria that he or she achieved with lower performance than other hospitals.